Does the property revert to the donor if the donee does not execute the established charge or mode? - Mendoza Vásquez, Enrique (2022)
The Peruvian Civil Code, unlike the French, Spanish and Argentinean Codes, does not contemplate the revocation of the donation for noncompliance with the charge. This article is justified because even though the Peruvian Civil Code does not sanction the non-compliance with the charge with the revocation or termination of the donation, the reality can sometimes overflow the normative framework. The judge is not allowed to disregard the text of the law, since it would take away all sense, but it is up to him to find the solution to the problem within its limits, without denaturalizing it or leaving it aside with interpretations that are not in accordance with its legal nature.